Analisis Perilaku Sanitasi Lingkungan Masyarakat Kelurahan Bagan Deli Kecamatan Medan Belawan - Nanda, Meutia; Erwina, Bella Putri; Rahman, Aulia Arief; Zahra, Mauliza; Maziaturrahman, Maziaturrahman; Purwadi, Puspa Ofri Anti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Efforts to improve environmental health and promote healthy living behaviors among the community have a significant impact on public health. Issues related to toilets and waste disposal are very disruptive. Environmental sanitation is human efforts to maintain health by creating a healthy living environment. This study aims to understand the behavior of environmental sanitation in the community of Bagan Deli, Medan Belawan District. The research used a quantitative descriptive method with a sample size of 82 people, determined using the Slovin formula with a margin of error of 5% (0.05). Data collection was obtained through observation and interviews using a questionnaire. The results show that 39 people (47.6%) do not have toilet facilities, 25 people (30.5%) have toilet facilities but do not meet the requirements, and 18 people (22%) have adequate toilet facilities. A total of 74 people (90.2%) have bathrooms inside their homes, 76 people (78%) have a clean water source from a borehole, and 18 people (22%) have a water source from the public water supply (PDAM). Furthermore, 81 people (98.8%) dispose of bathroom waste directly into the sea, and 74 people (90.2%) dispose of garbage directly into the sea. From this research, it can be concluded that many people in Bagan Deli, Medan Belawan District still do not have family toilet facilities, proper bathroom waste disposal, and garbage disposal areas, resulting in health problems due to poor sanitation.